A Descriptive Study to Assess the Level of Knowledge on Birth Preparedness among Primi-gravida Mothers (Journal of Pharmaceutical Negative Results, 2022)
Background: Birth preparedness incorporates the system of planning for an ordinary birth and looking forward to the actions needed in case of an emergency.Aim: The present aim was to assess the existing level of knowledge on birth preparedness among primigravida mothers who attended antenatal clinic at Saveetha Medical College and Hospital.Materials and Methods: A quantitative approach with descriptive research design was adopted for the present study. 60 primigravida mothers (n=60) were recruited by using the non-probability purposive sampling technique. A self-structured questionnaire method was used to collect both demographic data and the existing level of knowledge on birth preparedness during pregnancy among primigravida mothers.Results: Among 60 study participants, the mean score on existing level of knowledge on birth preparedness among primigravida mothers was found to be 13.08 with standard deviation 4.22. Hence the findings of current study concluded that, primi-gravida mothers had an average level of knowledge on birth preparedness during their pregnancy period.